2014
DOI: 10.1177/0961203314555353
|View full text |Cite
|
Sign up to set email alerts
|

Systemic lupus erythematous and clinical outcomes in peritoneal dialysis

Abstract: PD therapy was shown to be a safe and equally successful therapy for SLE patients compared to matched non-SLE patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…There appear to be no differences according to the primary disease, even with lupus nephritis or polycystic kidney disease [413,414]. A retrospective study on the incidence of peritonitis in Japan in 1996 reported a value of 0.23/patient/year [415].…”
Section: Explanationmentioning
confidence: 99%
“…There appear to be no differences according to the primary disease, even with lupus nephritis or polycystic kidney disease [413,414]. A retrospective study on the incidence of peritonitis in Japan in 1996 reported a value of 0.23/patient/year [415].…”
Section: Explanationmentioning
confidence: 99%
“…Liver cancer is the sixth most common cancer worldwide, accounting for 5.6% of the total cases diagnosed in 2012 (1)(2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
“…In developed countries, liver cancer is the sixth leading cause of cancer-associated mortality among men. In 2012, an estimated 782,000 new liver cancer cases and 745,000 deaths occurred globally, with >50% of the total cases and deaths reported in China (2)(3)(4)(5). In China, liver cancer is the fourth most common cancer and the third leading cause of cancer-associated mortality (5).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that patients with LN undergoing PD have a poor prognosis associated with higher hospitalization and infection rates (24). However, a prospective observational study from the BRAZPD II cohort showed that systemic lupus erythematosus (SLE) patients on PD had similar patient and technique survival (5). The controversial results may be mainly attributed to the selection bias in different districts, different socio-economic situations and follow-up periods (6).…”
mentioning
confidence: 99%